Effect and Mechanism of Mycobacterium tuberculosis Lipoprotein LpqH in NLRP3 Inflammasome Activation in Mouse Ana-1 Macrophage. (5th January 2021) - Liu, Liting; Zhai, Kaixin; Chen, Yue; Chen, Xiaowen; Wang, Guofu; Wu, Lixian
Abstract : The study is aimed at investigating the role and mechanism of LpqH of Mycobacterium tuberculosis in the activation of NLRP3 inflammasome in mouse Ana-1 macrophages. ExPASy-ProtParam, PHYRE2, ABCpred, and SYFPEITHI were used to predict and analyze the physicochemical properties, protein structure, and B cell/T cell-associated epitopes of LpqH protein. The recombinant LpqH protein was purified, and its immunoreactivity was analyzed with western blot. The LPS-treated mouse Ana-1 macrophages were incubated with purified LpqH protein directly. The expression of NLRP3, ASC, and caspase-1 protein was detected by western blot. The secretion of IL-1 β was detected by ELISA, and LDH was detected by a kit. Cell death was detected by flow cytometry. LpqH consisted of 159 amino acids and was a hydrophobic protein with stable properties. Its secondary structure contained 47% random coils, 53% β -sheets, and 3% α -helix. The tertiary structure showed a relatively loose spatial conformation. Additionally, it had 8 B cell epitopes (score > 0.8 ) and 10 CTL cell epitopes (score ≥ 20 ). The recombinant LpqH, which had strong immunoreactivity, significantly increased the levels of NLRP3, ASC, and caspase-1 p20 (P < 0.01 ) and promoted the secretion of IL-1 β by the cells (P < 0.01 ). In addition, high concentration of KCl significantly inhibited the effect of LpqH on mouse Ana-1 macrophages and reduced the expression of NLRP3, ASC, and caspase-1 p20 (P < 0.01 ). However, there was no significant change in LDH (P > 0.05 ). Meanwhile, LpqH protein did not cause additional cell death (P > 0.05 ). LpqH protein has good immunogenicity and can activate the NLRP3 inflammasome through the potassium efflux pathway without causing cell death.